IDENTIFICATION OF THE LOMBOK EARTHQUAKE SOURCE MECHANISM M_W 6.9 AND M_W 7.0 ON AUGUST 5 AND 9 2018 - Priadi, Ramadhan (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2020)
Significant earthquakes with magnitudes ranging from M 5.8 to 7.0 occurred in Lombok in the period July to August 2018. 2 earthquake events occurred in a row namely  6.9 on August 5, 2018 (11:46:38 UTC) and  7.0 on August 9, 2018 (14:56:28 UTC). This phenomenon is very rare because earthquakes require a relatively long time to accumulate energy before being released. Based on the uniqueness, slip modeling is carried out in the fracture plane to determine the distribution of energy accumulation zones represented by asperity. Modeling is done by teleseismic body wave inversion at low frequencies. Modeling results show that the earthquake asperity zone of  6.9 is 0 km in strike direction and -18 km width in dip direction with a maximum slip of 1.3 m. While the results of earthquake modeling  7.0 the asperity zone is at -36 km in the strike direction and -7 km in the dip direction. The  7.0 earthquake shows the distribution of the dominant slip almost perpendicularly upward. The highest aspiration zone is in the up-dip portion of the earthquake hypocenter. These results indicate the earthquake slip vectors  6.9 pointing to the earthquake fault plane  7.0. Modeling results also indicate that a significant earthquake in Lombok does not have a single asperity, but is distributed in the fault plane. This is thought to be due to the condition of brittle rocks and enlargement that is limited by time and space.